Comparative analysis of databases working under the control of Windows system - Stets, Serhii; Kozieł, Grzegorz (Journal of Computer Sciences Institute, 2019)
The aim of this paper is to conduct research on the most popular database management systems such as MySQL, PostgreSQL and Firebird in terms of query performance, CPU load and disk usage. At the first stage, the analysis of the popularity of databases was carried out. In the second stage an application was created that allows for communication with selected databases. At the third stage, tests were carried out using a written application and analysis of results.